OXYGEN-HYDROGEN SULFIDE COEXISTENCE LAYER IN THE PELAGIC ZONE OF THE BLACK SEA - Volkov I.I.; Vinogradov M.Ye.; Lukashov Yu.F. (My University, 1990)
In the summer (July-September) of 1989, the question of the coexistence of hydrogen sulfide and oxygen in the Black Sea was investigated in detail during a cruise of the R/V Dmitriy Mendeleyev. Reliably detectable oxygen is present to a depth of 150 to 170 m, where the H2S content exceeds 1 mg/liter. The zero-oxygen depths obtained in parallel samples by the three methods are identical in all cases. The upper boundary of the hydrogen sulfide layer is identifiable with great accuracy and ranges from 115 to 140 m. The thickness of the oxygen-H2S coexistence layer as customarily defined varies from station to station and is between 30 and 45 to 50 m. We believe that the data constitute rather sound evidence that the reduced sulfur compounds that are identifiable in the oxygen-deficient layer and the lower oxycline of the Black Sea are formed in situ and are not reoxidized to sulfate there. They are in no way the product of upward movement of hydrogen sulfide from the deep layer and should not be lumped together with this hydrogen sulfide when analyzing the dynamics of the upper boundary of hydrogen sulfide-containing water.